A Group Intervention for Prospective First-Generation College Students: Application With an Urban, African American Population. Issue 1 (January 2020) - Malott, Krista; Havlik, Stacey; Gosai, Shivam; Diaz Davila, Jose
We applied a qualitative inquiry to explore the experiences of African American youth engaging in a group intervention at an urban high school. Group topics were tailored to the needs of prospective first-generation college students to enhance youth social and academic capitol and identity strengthening. Experiences included changed perspectives and increased knowledge of the college-going experience that, in turn, increased participant sense of efficacy in completing college. We discuss implications for school counselors.